Estudio de fuentes de rayos X asociadas a la fuente de rayos γ no identificada 2FGL J0534.8-0548 - Kornecki, Paula (2016)
In this paper, we present a preliminary study of four point-like X-ray sources detected with XMM-Newton. Three of them lie within the ellipse corresponding to the 95 confidence contour of the unidentified -ray source 2FGL J0534.80548c, detected with the Fermi telescope. The fourth, named 2XMM J053514.8055143 and identified with a binary system, is located outside the ellipse. In order to know the nature of the ray source and a possible physical connection to the X-ray sources, we used XMM-Newton observations (ID 0690200501) to study morphological, temporal and spectral properties of all sources in the energy range 0.3 to 12 keV. The analysis shows that two of the sources present temporal variability and that all have spectra dominated by prominent emission lines, which can be adequately modeled by at least two different thermal models.